Chapter Feasibility study of a cold ironing system and district heating in port area - Colarossi, Daniele (Proceedings e report, 2020)
Cold ironing is a technology to reduce polluting emissions covering the energy demand of berthed ships in port to shut down their auxiliary engines. A feasibility study for the port of Ancona is proposed. A cogeneration plant provides electricity to ships, and the recovered heat waste is used in a district heating network. Results show that a 1.5MW and 2MW cogenerator covers 83% and 92% of the electrical need of ships respectively, and 61% and 74% of the thermal need of the involved buildings over the analysed period. The scenarios have been economically evaluated and prove to be feasible.